Self-compacting nano-modified recycled coral aggregate concrete and its preparation method and application

By adopting the preparation method of self-finished nanomodified regenerated coral aggregate concrete in island and reef projects, the existing coral concrete has been solved, and high-strength, good early strength and environmentally friendly concrete has been achieved, which is suitable for emergency repair and reconstruction of island and reef projects.

CN118459171BActive Publication Date: 2025-04-11XIANGTAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410569150.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-04-11
Estimated Expiration
2044-05-09

AI Technical Summary

Technical Problem

Existing coral concrete has problems in island and reef projects with low strength, insufficient early strength, durability and sustainability, and is difficult to meet the high requirements in the marine environment.

Method used

The preparation method of self-finished nanomodified regenerated coral aggregate concrete is adopted to form high-strength and good early strength concrete by soaking regenerated coral aggregate, adding nanosilicon dioxide and nanomaterial dispersant, sonication, mixing gelling materials and water reducing agents.

Benefits of technology

Concrete with high strength (compressive strength reaches more than 80MPa), good early strength, stable chemical properties, excellent economical and environmental protection is achieved, and is suitable for emergency repair and reconstruction of island and reef projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118459171B_ABST
    Figure CN118459171B_ABST
Patent Text Reader

Abstract

The invention discloses a self-compacting nano-modified recycled coral aggregate concrete and a preparation method and application thereof. The preparation method comprises preparing primary reinforced recycled coral coarse and fine aggregates, preparing a seawater solution containing a second nano-silicon dioxide, adding 2 / 3 of the seawater solution into a cementitious material prepared by mixing ordinary Portland cement, silica fume and fly ash to obtain cement paste, adding a first water reducer, adding primary reinforced recycled coral coarse aggregate for secondary reinforcement, adding a second water reducer and the remaining seawater solution containing a second nano-silicon dioxide, adding primary reinforced recycled coral fine aggregate into the obtained gel state concrete mixture, loading into a mold, standing, demoulding, and curing to obtain self-compacting nano-modified recycled coral aggregate concrete. The concrete prepared by the invention has the advantages of good early strength, high strength, stable chemical properties, excellent economy and environmental protection, and excellent working performance, and is suitable for island and reef engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building engineering materials, and in particular relates to self-compacting nano-modified recycled coral aggregate concrete and a preparation method and application thereof. Background Art

[0002] The ocean is rich in minerals, oil, natural gas and many other resources, and the development and utilization of the ocean is of vital importance. In the current global pattern, over-exploitation has accelerated the depletion of land energy resources. In order to enhance the development capacity of offshore resources, offshore oil drilling, offshore engineering platforms and island infrastructure construction have begun to be vigorously promoted, which has also brought about a shortage of construction materials. If all raw materials are transported and imported from land, the large-scale maintenance costs will be very high. In addition, this will also bring a lot of unpredictable variables to the construction time. Therefore, it is important to accelerate the construction of island projects. However, global warming threatens the coral reef ecosystem, and the marine ecological balance has been seriously affected. In addition, island projects are also faced with the risk of emergencies such as earthquakes, shocks and waves, and the corresponding safety and stability issues need to be addressed.

[0003] In this context, how to deal with these emergencies and ensure the safety and stability of island and reef engineering construction has become an important issue. Shortening the repair and construction period is the goal to be pursued, and at the same time, requirements are also put forward for the strength of construction materials. Researchers used coral reef stones as aggregates to prepare coral aggregate concrete and studied its mechanical properties. However, coral concrete may have many defects: the strength of coral concrete is relatively low, usually between 20MPa and 40MPa, which is lower than that of traditional concrete, which may limit its use in certain structural applications. Even if coral concrete with a strength of more than 50MPa can be prepared, it is enhanced by means of fibers, low water-cement ratio, etc., but this practice may reduce the workability of the concrete, that is, the working performance of the concrete is poor. Secondly, due to the special properties of coral aggregate, such as porosity and the presence of organic matter, it may be sensitive to long-term use and environmental conditions, which may lead to durability problems. The sustainability of coral concrete also needs to be considered. When using coral aggregate, it is necessary to ensure that its collection and use comply with the principles of environmental and ecological protection to avoid irreversible damage to the marine ecosystem. Island and reef projects have high requirements for construction materials, and they need to be able to resist factors such as marine environmental erosion, wave impact and underwater scouring. In island and reef projects, the performance of conventional concrete cannot effectively resist seawater erosion, wave impact and underwater scouring, and cannot meet the special requirements of the marine environment, which may cause damage, corrosion and destruction of the structure and shorten the service life of the structure. In island construction, island and reef projects need to withstand long-term marine environmental erosion and wave impact. Therefore, concrete needs to have higher early strength and mechanical properties requirements in order to resist the influence of marine environmental factors such as salt water erosion, chloride ion penetration and freeze-thaw cycles. However, existing coral concrete either has early strength but generally low strength, or has strength but the early strength is not obvious. Therefore, further research and development of building materials suitable for island and reef projects is needed to ensure the sustainable development of the project. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a self-compacting nano-modified recycled coral aggregate concrete suitable for island and reef engineering, which has excellent early strength, high strength, stable chemical properties, excellent economy and environmental protection, and excellent working performance, as well as a preparation method and application thereof.

[0005] In order to solve the above technical problems, the present invention proposes the following solutions.

[0006] A method for preparing self-compacting nano-modified recycled coral aggregate concrete comprises the following steps:

[0007] (1) Weighing 2690 to 2740 parts of regenerated coral coarse aggregate, 2170 to 2185 parts of regenerated coral fine aggregate, 49 to 50 parts of first nano-silicon dioxide, 15 to 20 parts of first nano-material dispersant, and 4990 to 5000 parts of first seawater, by mass, adding the first nano-silicon dioxide and the first nano-material dispersant to the first seawater to obtain a seawater solution containing the first nano-silicon dioxide, and then adding the regenerated coral coarse aggregate and the regenerated coral fine aggregate to the seawater solution containing the first nano-silicon dioxide, respectively. After soaking, the aggregate is taken out and air-dried to constant weight to obtain primary reinforced regenerated coral coarse aggregate and primary reinforced regenerated coral fine aggregate respectively, and the primary reinforced regenerated coral coarse aggregate is sieved to obtain primary reinforced regenerated coral coarse aggregate A and primary reinforced regenerated coral coarse aggregate B, wherein 9.5 mm ≤ the particle size of the primary reinforced regenerated coral coarse aggregate A ≤ 19 mm, 4.75 mm ≤ the particle size of the primary reinforced regenerated coral coarse aggregate B < 9.5 mm, and 0.03 mm ≤ the particle size of the primary reinforced regenerated coral fine aggregate < 4.75 mm;

[0008] (2) pouring the second nano-silicon dioxide into the second seawater, adding a second nano-material dispersant, and fully dissolving the second nano-silicon dioxide in the second seawater by ultrasonic treatment until a transparent liquid state is formed, thereby obtaining a seawater solution containing the second nano-silicon dioxide;

[0009] (3) mixing and stirring ordinary Portland cement, silica fume and fly ash to obtain a cementitious material, and then adding two-thirds of the seawater solution containing the second nano-silicon dioxide and continuing to stir to obtain a cement paste containing the seawater solution of silicon dioxide;

[0010] (4) adding the first water reducing agent to the cement paste and stirring thoroughly to obtain a cement paste gel;

[0011] (5) adding the primary reinforced recycled coral coarse aggregate A to the cement paste gel and stirring, then letting it stand, and then adding the primary reinforced recycled coral coarse aggregate B to perform secondary reinforcement to obtain a concrete mixture;

[0012] (6) adding the second water reducing agent and the remaining seawater solution containing the second nano-silicon dioxide to the concrete mixture, and stirring the concrete mixture to form a uniform gel state;

[0013] (7) adding the primary reinforced regenerated coral fine aggregate to the concrete mixture in a gel state obtained in step (6), stirring, placing into a mold, standing, demolding, and curing to obtain a self-compacting nano-modified regenerated coral aggregate concrete;

[0014] In the above steps (2) to (7), the raw materials are weighed in parts by mass as follows: 5.1 to 15.3 parts of the second nano-silicon dioxide, 598 to 605 parts of the second seawater, 5 to 8 parts of the second nano-material dispersant, 1.5 to 2 parts of the first water reducer, 1542 to 1564 parts of ordinary Portland cement, 152 to 158 parts of silica fume, 178 to 188 parts of fly ash, 2690 to 2740 parts of the primary reinforced regenerated coral coarse aggregate, 2 to 2.7 parts of the second water reducer, and 2140 to 2180 parts of the primary reinforced regenerated coral fine aggregate. More preferably, the second nano-silicon dioxide is 9.5 to 10.3 parts.

[0015] The method for preparing the self-compacting nano-modified recycled coral aggregate concrete is preferably such that in step (1), the soaking time is 24h to 25h, in step (3), the continued stirring time is 2min to 3min, in step (4), the sufficient stirring time is 1min to 2min, in step (5), the stirring time is 1min to 3min, the static time is 30s to 60s, in step (6), the stirring time is 2min to 4min, and in step (7), the standing time is 24h to 25h.

[0016] The method for preparing the self-compacting nano-modified recycled coral aggregate concrete is preferably such that in step (1), the source of the recycled coral coarse aggregate is a discarded coral sand cement-based composite material obtained by crushing, screening, washing and drying with a jaw crusher, and the discarded coral sand cement-based composite material is characterized by: the mechanical property is to achieve a compressive strength value of 50 MPa or more at 28 days of age, and the components are calculated by mass, including 705 to 712 parts of PO42.5 ordinary Portland cement, 249 to 254 parts of fly ash, 92 to 97 parts of silica fume, 1390 to 1376 parts of coral sand, 270 to 278 parts of artificial seawater, and a water-binder ratio of 0.25; the recycled coral coarse aggregate also has the following characteristics: 0 < moisture content ≤ 0.1%, and an apparent density of 2170 kg / m 3 ~2185kg / m 3 , bulk density is 1105kg / m 3 ~1125kg / m 3 , water absorption rate is 5.8% to 8.9%, 0<crushing value ≤ 15%; in the primary reinforced regenerated coral coarse aggregate, the mass fraction of the primary reinforced regenerated coral coarse aggregate A is 64% to 65%, and the mass fraction of the primary reinforced regenerated coral coarse aggregate B is 35% to 36%.

[0017] The method for preparing the self-compacting nano-modified recycled coral aggregate concrete is preferably such that in step (1), the source of the recycled coral fine aggregate is a discarded coral sand cement-based composite material crusher, and the particle size gradation of the recycled coral fine aggregate is 2.5mm<particle size≤5mm accounting for 1%, 1.25mm<particle size≤2.5mm accounting for 10%, 0.5mm<particle size≤1.25mm accounting for 20%, 0.3mm<particle size≤0.5mm accounting for 58%, and 0.1mm<particle size≤0.3mm accounting for 11%; the recycled coral fine aggregate also has the following characteristics: 0<water content≤0.3%, apparent density of 2520kg / m 3 ~2546kg / m 3 , bulk density is 1562kg / m 3 ~1575kg / m 3 The water absorption rate is 10.1% to 10.5%, the fineness modulus of the regenerated coral fine aggregate is 2.32, and the regenerated coral fine aggregate is fine sand.

[0018] In the method for preparing the self-compacting nano-modified recycled coral aggregate concrete, preferably, in step (1), the sand ratio of the concrete is 43.5% to 45.0%.

[0019] In the method for preparing the self-compacting nano-modified recycled coral aggregate concrete, preferably, the first seawater and the second seawater are both artificial seawater, and the artificial seawater is composed of water and the following components in the following concentrations: sodium chloride 24g·L -1 ~26g·L -1 , magnesium chloride 4g·L -1 ~5.5g·L -1 , sodium sulfate 4g·L -1 ~5g·L -1 , potassium chloride 1g·L -1 ~1.5g·L -1 , sodium bicarbonate 0.1 g·L -1 ~0.5g·L -1 , magnesium bromide 0.1 g·L -1 ~0.5g·L -1 ;

[0020] The ordinary Portland cement is PO52.5 Portland cement or C52.5 Portland cement;

[0021] The fly ash has the following characteristics: it is Class I fly ash, in the form of spherical particles, with a specific surface area of ​​1285m 2 / kg~1295m 2 / kg, water requirement is 97% to 99%, sphere density is 2.2g / cm 3 ~2.32g / cm 3, the content of spherical particles is 90% to 91%, and the fineness is 11% to 17%;

[0022] The silica fume has the following characteristics: specific surface area is 19400m 2 / kg~19500m 2 / kg, SiO2 content is 95% to 96.75%, water requirement ratio is 125%, moisture content is 0.4% to 0.5%, and burning vector is 3.5% to 3.7%;

[0023] The first water reducer and the second water reducer are both polycarboxylate water reducers, which are white powder particles with a solid content of 98%, a water reduction rate of 30% to 35%, a moisture content of 1.5% to 2.0%, and a bulk density of 0.65 g / cm 3 ~0.75g / cm 3 , pH value is 7.0, chloride ion content is 0-0.01%, alkali content is 0-1%, sodium sulfate content is 0.5%-1.6%, and fineness is 6.0% on a 300-micron square hole sieve.

[0024] In the method for preparing the self-compacting nano-modified recycled coral aggregate concrete, preferably, the particle size of the second nano-silicon dioxide is less than 20 nm, the particle size of the fly ash is 8 μm to 20 μm, the particle size of the silica ash is 0.1 μm to 0.3 μm, and the particle size of the ordinary Portland cement is 7 μm to 200 μm.

[0025] As a general technical concept, the present invention also provides a self-compacting nano-modified recycled coral aggregate concrete prepared by the above-mentioned preparation method.

[0026] The above-mentioned self-compacting nano-modified recycled coral aggregate concrete, preferably, has an expansion degree of 600mm to 700mm.

[0027] As a general technical concept, the present invention also provides a self-compacting nano-modified recycled coral aggregate concrete prepared by the above-mentioned preparation method or the application of the above-mentioned self-compacting nano-modified recycled coral aggregate concrete in the field of emergency repair and construction of coastal projects or island and reef projects.

[0028] In the present invention, the sand ratio is fine aggregate / (fine aggregate+coarse aggregate).

[0029] Compared with the prior art, the advantages of the present invention are:

[0030] (1) The concrete prepared by the present invention has good mechanical properties (high strength) and early strength properties. Among the static mechanical properties, the early strength is high, and the 28d cube compressive strength reaches more than 80MPa. The recycled aggregate method and preparation method strengthened by the present invention can be used to prepare high-strength recycled concrete, wherein the compressive strength can reach 80MPa. Compared with the existing technology (such as CN117263616A), its static compressive strength is increased by 20MPa, which can effectively defend against the impact of island and reef waves and housing needs, and at the same time has good early strength performance, which can be applied to the actual emergency repair and construction, renovation and reconstruction projects of islands and reefs.

[0031] (2) The concrete prepared by the present invention has better working performance than the existing technology. By measuring the slump value, it can be concluded that the slump value and expansion value of the concrete are higher than those of the existing technology. The good working performance of the concrete can flow freely and be distributed to the area that needs to be filled during the pouring process, avoiding quality defects such as cold slurry, faults and honeycomb surface. At the same time, the pumping requirements are met during the concrete pouring process, which better meets the actual needs of the project, is conducive to shortening the construction period and reducing construction costs.

[0032] (3) The concrete of the present invention has stable chemical properties and strong durability, and can effectively resist marine disasters such as coastal erosion.

[0033] (4) The aggregates used in the concrete prepared by the present invention are all recycled aggregates made from waste materials, which is beneficial to protecting natural resources and has the advantages of being low carbon and green.

[0034] (5) The proportion of aggregate in concrete materials usually accounts for 70%-80% of concrete. The coarse and fine aggregates used in the present invention are all prepared from island and reef projects and solid waste near the coast. There is no need to transport materials from land to islands and reefs, which can save expensive transportation costs and the cost of purchasing traditional aggregates. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a physical picture of the expansion test of the self-compacting nano-modified recycled coral aggregate concrete prepared in Example 1 of the present invention.

[0036] Figure 2 This is a microscopic morphology of the recycled coral coarse aggregate in the self-compacting nano-modified recycled coral aggregate concrete prepared in Example 1 of the present invention.

[0037] Figure 3 This is a microscopic morphology of the recycled coral fine aggregate in the self-compacting nano-modified recycled coral aggregate concrete prepared in Example 1 of the present invention.

[0038] Figure 4This is a diagram showing the filling effect of nano-silica and cement mortar matrix on the microstructure pores of coral particles in the self-compacting nano-modified recycled coral aggregate concrete prepared in Example 1 of the present invention.

[0039] Figure 5 The microstructure of the interface transition zone between aggregate and cement mortar in the self-compacting nano-modified recycled coral aggregate concrete prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. The materials and instruments used in the following embodiments are all commercially available.

[0041] In the following embodiments (Example 1-Example 3):

[0042] The source of the recycled coral coarse aggregate is the waste coral sand cement-based composite material obtained by crushing, screening, washing and drying with a jaw crusher. The characteristics of the waste coral sand cement-based composite material are as follows: the mechanical property is to achieve a compressive strength value of more than 50MPa at the age of 28 days, and the components are calculated by mass, including 712 parts of PO42.5 ordinary silicate cement, 254 parts of fly ash, 92 parts of silica fume, 1376 parts of coral sand, 275 parts of artificial seawater, and a water-binder ratio of 0.25; the recycled coral coarse aggregate also has the following characteristics: 0<water content≤0.1%, apparent density of 2175kg / m 3 , bulk density is 1120kg / m 3 , water absorption is 6.2%, 0<crushing value ≤9%.

[0043] The source of recycled coral fine aggregate is the abandoned coral sand cement-based composite material crusher. The particle size distribution of recycled coral fine aggregate is 2.5mm<particle size ≤5mm accounting for 1%, 1.25mm<particle size ≤2.5mm accounting for 10%, 0.5mm<particle size ≤1.25mm accounting for 20%, 0.3mm<particle size ≤0.5mm accounting for 58%, 0.1mm<particle size ≤0.3mm accounting for 11%; recycled coral fine aggregate also has the following characteristics: moisture content is 0.1%, apparent density is 2540kg / m 3 , bulk density is 1572kg / m 3 The water absorption rate is 10.1%, the fineness modulus of the recycled coral fine aggregate is 2.32, and the recycled coral fine aggregate is fine sand.

[0044] The sand ratio of concrete is 44.4%.

[0045] The first seawater and the second seawater are both artificial seawater, which are composed of water and the following components: sodium chloride 25g·L -1 , magnesium chloride 5.0g·L-1 , sodium sulfate 4g·L -1 , potassium chloride 1.0 g·L -1 , sodium bicarbonate 0.1 g·L -1 , magnesium bromide 0.1 g·L -1 .

[0046] Ordinary Portland cement is PO52.5 Portland cement.

[0047] Fly ash has the following characteristics: It is Class I fly ash, in the form of spherical particles, with a specific surface area of ​​1292m 2 / kg, water requirement is 99%, sphere density is 2.31g / cm 3 , the spherical particle content is 91% and the fineness is 16%.

[0048] Silica fume has the following characteristics: Specific surface area is 19488m 2 / kg, SiO2 content is 96%, water requirement ratio is 125%, moisture content is 0.4%, and burning vector is 3.6%.

[0049] The first water reducer and the second water reducer are both polycarboxylate water reducers. The polycarboxylate water reducer is a white powder with a solid content of 98%, a water reduction rate of 30%, a moisture content of 1.5%, and a bulk density of 0.70 g / cm 3 , pH value is 7.0, chloride ion content is 0, alkali content is 0, sodium sulfate content is 1.0%, and the fineness is 6.0% on a 300-micron square hole sieve.

[0050] The particle size of the second nano-silicon dioxide is less than 20 nm, the particle size of the fly ash is 8 μm to 20 μm, the particle size of the silica ash is 0.1 μm to 0.3 μm, and the particle size of the ordinary Portland cement is 7 μm to 200 μm.

[0051] Example 1

[0052] A method for preparing a self-compacting nano-modified recycled coral aggregate concrete of the present invention comprises the following steps:

[0053] (1) 2735 parts of regenerated coral coarse aggregate, 2180 parts of regenerated coral fine aggregate, 50 parts of first nano-silicon dioxide, 18 parts of first nano-material dispersant, and 4995 parts of first seawater were weighed by mass. The first nano-silicon dioxide and the first nano-material dispersant were added to the first seawater to obtain a seawater solution containing the first nano-silicon dioxide. The regenerated coral coarse aggregate and the regenerated coral fine aggregate were then added to the seawater solution containing the first nano-silicon dioxide and soaked. After soaking, the aggregates were taken out and air-dried to constant weight to obtain a primary reinforced regenerated coral coarse aggregate and a primary reinforced regenerated coral fine aggregate, respectively. The primary reinforced regenerated coral coarse aggregate was sieved to obtain a primary reinforced regenerated coral coarse aggregate A and a primary reinforced regenerated coral coarse aggregate B. The particle size of the primary reinforced regenerated coral coarse aggregate A was 9.5 mm ≤ ≤ 19 mm, the particle size of the primary reinforced regenerated coral coarse aggregate B was 4.75 mm ≤ < 9.5 mm, and the particle size of the primary reinforced regenerated coral fine aggregate was 0.03 mm ≤ < 4.75 mm.

[0054] The raw materials are weighed according to the following parts by mass: 10.2 parts of the second nano-silicon dioxide, 604 parts of the second seawater, 5 parts of the second nano-material dispersant, 2 parts of the first water reducing agent, 1562 parts of ordinary Portland cement, 155 parts of silica fume, 185 parts of fly ash, 2735 parts of primary reinforced regenerated coral coarse aggregate, 2.5 parts of the second water reducing agent, and 2140 parts of primary reinforced regenerated coral fine aggregate; in the primary reinforced regenerated coral coarse aggregate, the mass fraction of the primary reinforced regenerated coral coarse aggregate A is 64%, and the mass fraction of the primary reinforced regenerated coral coarse aggregate B is 36%.

[0055] (2) pouring the second nano-silicon dioxide into the second seawater, adding the second nano-material dispersant, and fully dissolving the second nano-silicon dioxide in the second seawater by ultrasonic treatment until a transparent liquid state is formed, thereby obtaining a seawater solution containing the second nano-silicon dioxide;

[0056] (3) mixing and stirring the silicate cement, silica fume and fly ash to obtain a cementitious material, and then adding two-thirds of the seawater solution containing the second nano-silicon dioxide and continuing to stir to obtain a cement paste containing the seawater solution of silicon dioxide;

[0057] (4) adding the first water reducing agent to the cement paste and stirring thoroughly to obtain a cement paste gel;

[0058] (5) adding the primary reinforced recycled coral coarse aggregate A to the cement paste gel and stirring evenly, then letting it stand, and then adding the primary reinforced recycled coral coarse aggregate B to perform secondary reinforcement to obtain a concrete mixture, so that the cement paste can penetrate and fill the surface and pores of the aggregate;

[0059] (6) adding the second water reducing agent and the remaining (one third) seawater solution containing the second nano-silicon dioxide to the concrete mixture, and stirring the concrete mixture to form a uniform gel state;

[0060] (7) Adding the primary reinforced recycled coral fine aggregate to the concrete mixture in the gel state obtained in step (6), stirring, placing into a mold, standing, demolding, and curing to obtain a self-compacting nano-modified recycled coral aggregate concrete.

[0061] In this embodiment, the soaking time in step (1) is 24 hours, the continuous stirring time in step (3) is 3 minutes, the sufficient stirring time in step (4) is 2 minutes, the stirring time in step (5) is 3 minutes, the standing time is 30 seconds, the stirring time in step (6) is 4 minutes, and the standing time in step (7) is 24 hours.

[0062] It has been determined that the expansion of the self-compacting nano-modified recycled coral aggregate concrete prepared in this embodiment is 650 mm. Figure 1 The performance of the self-compacting nano-modified recycled coral aggregate concrete is shown in Table 1. It can be seen from Table 1 that the concrete strength is up to 82.9MPa, which meets the requirements of important structural grades. Figure 2 , Figure 3 It can be seen that after the nano-strengthening process, the microstructure of the aggregate is improved. Figure 4 It can be seen that the pore structure of the coral has been filled to a certain extent, the aggregate has been strengthened, and at the same time, Figure 5 It can be seen that the interface transition zone between the mortar matrix and the aggregate of the concrete prepared in this embodiment is densely connected without obvious faults, thus showing good microscopic properties. The concrete has excellent comprehensive properties and can be applied to the emergency repair and construction of coastal projects or island and reef projects.

[0063] Example 2

[0064] A method for preparing the self-compacting nano-modified recycled coral aggregate concrete of the present invention is basically the same as Example 1, except that the second nano-silicon dioxide is 5.1 parts and the second nano-material dispersant is 2.5 parts. The properties of the self-compacting nano-modified recycled coral aggregate concrete are shown in Table 1.

[0065] Example 3

[0066] A method for preparing the self-compacting nano-modified recycled coral aggregate concrete of the present invention is basically the same as Example 1, except that the second nano-silicon dioxide is 15.3 parts and the second nano-material dispersant is 7.5 parts. The properties of the self-compacting nano-modified recycled coral aggregate concrete are shown in Table 1.

[0067] Comparative Example 1

[0068] A method for preparing nano-modified recycled coral aggregate concrete is basically the same as that of Example 1, except that neither the recycled coral coarse aggregate nor the recycled coral fine aggregate has undergone a primary strengthening process.

[0069] The specific steps include:

[0070] (1) Weigh the following raw materials in parts by weight: 10.2 parts of the second nano-silicon dioxide, 604 parts of the second seawater, 5 parts of the second nano-material dispersant, 2 parts of the first water reducer, 1562 parts of ordinary Portland cement, 155 parts of silica fume, 185 parts of fly ash, 2735 parts of recycled coral coarse aggregate, 2.5 parts of the second water reducer, and 2140 parts of recycled coral fine aggregate; wherein the recycled coral coarse aggregate is sieved to obtain recycled coral coarse aggregate A and recycled coral coarse aggregate B, the particle size of the recycled coral coarse aggregate A is 9.5 mm≤≤19 mm, the particle size of the recycled coral coarse aggregate B is 4.75 mm≤<9.5 mm, and the particle size of the recycled coral fine aggregate is 0.03 mm≤<4.75 mm.

[0071] (2) Pour the weighed second nano-silicon dioxide into the second seawater, add the second nano-material dispersant, and use an ultrasonic cleaning machine dissolution device to fully dissolve the second nano-silicon dioxide in the second seawater, so that it becomes a transparent liquid state after dissolution.

[0072] (3) PO52.5 silicate cement, silica fume and fly ash are mixed and stirred evenly to obtain a cementitious material, and then two-thirds of seawater dissolved with the second nano-silicon dioxide is added and stirred continuously to obtain a cement paste in which the second nano-silicon dioxide seawater solution is dissolved.

[0073] (4) Add the first water reducing agent into the cement paste material and stir thoroughly to obtain a cement paste gel.

[0074] (5) adding the recycled coral coarse aggregate A to the cement paste gel and stirring, then letting it stand, and then adding the recycled coral coarse aggregate B to obtain a concrete mixture;

[0075] (6) adding the second water reducing agent and the remaining seawater in which the second nano-silicon dioxide is dissolved to the concrete mixture, and stirring the mixture to form a uniform gel state;

[0076] (7) Adding recycled coral fine aggregate to the concrete mixture in a gel state obtained in step (6), stirring evenly, placing into a mold, letting it stand, demolding, and curing to obtain nano-modified recycled coral aggregate concrete.

[0077] The properties of the nano-modified recycled coral aggregate concrete prepared in this comparative example are shown in Table 1. Compared with Example 1, since the recycled coral coarse aggregate and the recycled coral fine aggregate were not reinforced once during the concrete preparation process, the compressive strength of the prepared concrete was 71.4 MPa, which was 11.8% lower than that of Example 1.

[0078] In this comparative example, the time for continued stirring in step (3) is 3 minutes, the time for sufficient stirring in step (4) is 2 minutes, the time for stirring in step (5) is 3 minutes, the time for standing is 30 seconds, the time for stirring in step (6) is 4 minutes, and the time for standing in step (7) is 24 hours.

[0079] Comparative Example 2

[0080] A method for preparing nano-modified recycled coral aggregate concrete is basically the same as Example 1, except that the second nano-silicon dioxide and the second nano-material dispersant are not added. The properties of the nano-modified recycled coral aggregate concrete prepared in this comparative example are shown in Table 1.

[0081] Comparative Example 3

[0082] A method for preparing nano-modified recycled coral aggregate concrete is basically the same as Example 1, except that step (2) is not performed, and in step (6), the second nano-silica is directly added to the concrete mixture. The properties of the nano-modified recycled coral aggregate concrete prepared in this comparative example are shown in Table 1.

[0083] Table 1 Concrete performance test results prepared by Examples 1-3 and Comparative Examples 1-3

[0084]

[0085] It can be seen from the above table that Example 1 has the highest compressive strength, indicating that Example 1 has the best second nano-silica dosage and the best reinforcement effect. Compared with Comparative Examples 1-3, Examples 1-3 have obvious improvements in early strength and 28-day compressive strength. This is mainly due to the primary reinforcement of the coarse and fine aggregates of the regenerated coral, the secondary reinforcement of the second nano-silica and the appropriate addition time, which enable the method of the present invention to significantly improve the mechanical properties of concrete.

[0086] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a self-compacting nano-modified recycled coral aggregate concrete, characterized in that: The following steps are involved: (1) Weighing 2690 to 2740 parts of regenerated coral coarse aggregate, 2170 to 2185 parts of regenerated coral fine aggregate, 49 to 50 parts of first nano-silicon dioxide, 15 to 20 parts of first nano-material dispersant, and 4990 to 5000 parts of first seawater, by mass, adding the first nano-silicon dioxide and the first nano-material dispersant to the first seawater to obtain a seawater solution containing the first nano-silicon dioxide, and then adding the regenerated coral coarse aggregate and the regenerated coral fine aggregate to the seawater solution containing the first nano-silicon dioxide, respectively. After soaking, the aggregate is taken out and air-dried to constant weight to obtain primary reinforced regenerated coral coarse aggregate and primary reinforced regenerated coral fine aggregate respectively, and the primary reinforced regenerated coral coarse aggregate is sieved to obtain primary reinforced regenerated coral coarse aggregate A and primary reinforced regenerated coral coarse aggregate B, wherein 9.5 mm ≤ the particle size of the primary reinforced regenerated coral coarse aggregate A ≤ 19 mm, 4.75 mm ≤ the particle size of the primary reinforced regenerated coral coarse aggregate B < 9.5 mm, and 0.03 mm ≤ the particle size of the primary reinforced regenerated coral fine aggregate < 4.75 mm; (2) pouring the second nano-silicon dioxide into the second seawater, adding a second nano-material dispersant, and fully dissolving the second nano-silicon dioxide in the second seawater by ultrasonic treatment until a transparent liquid state is formed, thereby obtaining a seawater solution containing the second nano-silicon dioxide; (3) mixing and stirring ordinary Portland cement, silica fume and fly ash to obtain a cementitious material, and then adding two-thirds of the seawater solution containing the second nano-silicon dioxide and continuing to stir to obtain a cement paste containing the seawater solution of silicon dioxide; (4) adding the first water reducing agent to the cement paste and stirring thoroughly to obtain a cement paste gel; (5) adding the primary reinforced recycled coral coarse aggregate A to the cement paste gel, stirring, and then letting it stand, and then adding the primary reinforced recycled coral coarse aggregate B to perform secondary reinforcement to obtain a concrete mixture; (6) adding the second water reducing agent and the remaining seawater solution containing the second nano-silicon dioxide to the concrete mixture, and stirring the concrete mixture to form a uniform gel state; (7) adding the primary reinforced recycled coral fine aggregate to the concrete mixture in a gel state obtained in step (6), stirring, placing into a mold, allowing to stand, demoulding, and curing, to obtain a self-compacting nano-modified recycled coral aggregate concrete; In the above steps (2) to (7), the raw materials are weighed in parts by mass as follows: 5.1 parts to 15.3 parts of the second nano-silicon dioxide, 598 parts to 605 parts of the second seawater, 5 parts to 8 parts of the second nano-material dispersant, 1.5 parts to 2 parts of the first water reducer, 1542 parts to 1564 parts of ordinary Portland cement, 152 parts to 158 parts of silica fume, 178 parts to 188 parts of fly ash, 2690 parts to 2740 parts of the primary reinforced regenerated coral coarse aggregate, 2 parts to 2.7 parts of the second water reducer, and 2140 parts to 2180 parts of the primary reinforced regenerated coral fine aggregate; In step (1), the source of the regenerated coral coarse aggregate is the waste coral sand cement-based composite material obtained by crushing, screening, washing and drying with a jaw crusher. The waste coral sand cement-based composite material is characterized by: the mechanical property is to achieve a compressive strength value of 50 MPa or more at the age of 28 days, and the components, by mass, include 705 to 712 parts of PO42.5 ordinary Portland cement, 249 to 254 parts of fly ash, 92 to 97 parts of silica fume, 1390 to 1376 parts of coral sand, 270 to 278 parts of artificial seawater, and a water-cement ratio of 0.25; the regenerated coral coarse aggregate also has the following characteristics: 0 < moisture content ≤ 0.1%, apparent density of 2170 kg / m³ to 2185 kg / m³, and bulk density of 1105 kg / m³ to 1125 kg / m³. kg / m³, water absorption rate is 5.8% to 8.9%, 0<crushing value ≤ 15%; in the primary reinforced regenerated coral coarse aggregate, the mass fraction of the primary reinforced regenerated coral coarse aggregate A is 64% to 65%, and the mass fraction of the primary reinforced regenerated coral coarse aggregate B is 35% to 36%; In step (1), the source of the regenerated coral fine aggregate is the waste coral sand cement-based composite material crushed by a crusher, and the particle size gradation of the regenerated coral fine aggregate is 2.5mm<particle size≤5mm accounting for 1%, 1.25mm<particle size≤2.5mm accounting for 10%, 0.5mm<particle size≤1.25mm accounting for 20%, 0.3mm<particle size≤0.5mm accounting for 58%, and 0.1mm<particle size≤0.3mm accounting for 11%; the regenerated coral fine aggregate also has the following characteristics: 0<water content≤0.3%, apparent density of 2520kg / m³~2546kg / m³, bulk density of 1562 kg / m³~1575 kg / m³, water absorption of 10.1%~10.5%, fineness modulus of the regenerated coral fine aggregate is 2.32, and the regenerated coral fine aggregate is fine sand.

2. The method for preparing the self-compacting nano-modified recycled coral aggregate concrete according to claim 1, characterized in that: In step (1), the soaking time is 24 h to 25 h, in step (3), the continued stirring time is 2 min to 3 min, in step (4), the sufficient stirring time is 1 min to 2 min, in step (5), the stirring time is 1 min to 3 min, and the standing time is 30 s to 60 s, in step (6), the stirring time is 2 min to 4 min, and in step (7), the standing time is 24 h to 25 h.

3. The method for preparing the self-compacting nano-modified recycled coral aggregate concrete according to claim 1 or 2, characterized in that: In step (1), the sand content of the concrete is 43.5% to 45.0%.

4. The method for preparing the self-compacting nano-modified recycled coral aggregate concrete according to claim 1 or 2, characterized in that: The first seawater and the second seawater are both artificial seawater, which are composed of water and the following components: sodium chloride 24 g·L -1 ~26 g·L -1 , magnesium chloride 4 g·L -1 ~5.5 g·L -1 , sodium sulfate 4 g·L -1 ~5 g·L -1 , potassium chloride 1 g·L -1 ~1.5 g·L -1 , sodium bicarbonate 0.1 g·L -1 ~0.5 g·L -1 , magnesium bromide 0.1 g·L -1 ~0.5g·L -1 ; The ordinary Portland cement is PO52.5 Portland cement or C52.5 Portland cement; The fly ash has the following characteristics: it is Class I fly ash, in the form of spherical particles, with a specific surface area of ​​1285m 2 / kg~1295m 2 / kg, water requirement is 97% to 99%, sphere density is 2.2g / cm 3 ~2.32g / cm 3 , the content of spherical particles is 90% to 91%, and the fineness is 11% to 17%; The silica fume has the following characteristics: specific surface area is 19400m 2 / kg~19500m 2 / kg, SiO2 content is 95% to 96.75%, water requirement ratio is 125%, moisture content is 0.4% to 0.5%, and burning vector is 3.5% to 3.7%; The first water reducer and the second water reducer are both polycarboxylate water reducers, which are white powder particles with a solid content of 98%, a water reduction rate of 30% to 35%, a moisture content of 1.5% to 2.0%, a bulk density of 0.65 g / cm³ to 0.75 g / cm³, a pH value of 7.0, a chloride ion content of 0 to 0.01%, an alkali content of 0 to 1%, a sodium sulfate content of 0.5% to 1.6%, and a fineness of 6.0% on a 300-micron square hole sieve.

5. The method for preparing the self-compacting nano-modified recycled coral aggregate concrete according to claim 1 or 2, characterized in that: The particle size of the second nano-silicon dioxide is less than 20 nm, the particle size of the fly ash is 8 μm to 20 μm, the particle size of the silica fume is 0.1 μm to 0.3 μm, and the particle size of the ordinary Portland cement is 7 μm to 200 μm.

6. A self-compacting nano-modified recycled coral aggregate concrete prepared by the preparation method according to any one of claims 1 to 5.

7. The self-compacting nano-modified recycled coral aggregate concrete according to claim 6, characterized in that: The expansion degree of the self-compacting nano-modified recycled coral aggregate concrete is 600 mm to 700 mm.

8. Use of the self-compacting nano-modified recycled coral aggregate concrete prepared by the preparation method according to any one of claims 1 to 5 or the self-compacting nano-modified recycled coral aggregate concrete according to claim 6 or 7 in the field of emergency repair and construction of coastal projects or island and reef projects.

Citation Information

Patent Citations

  • High-strength coral aggregate concrete and preparation method thereof

    CN108218350A

  • Recycled coral aggregate concrete suitable for island engineering and preparation method of recycled coral aggregate concrete

    CN117263616A